The climate of rebellion in the early modern Ottoman Empire - White, Sam, 1980- (Studies in environment and history, 2011)
"This book tells how extreme cold and drought during the Little Ice Age along with rising population pressure and resource shortages created a serious rebellion in the Ottoman Empire in the 1590s. It argues that the rebellion was a major turning point for the Ottomans, reversing more than a century of imperial growth and expansion, and leading to millions of deaths. Over the 1600s, recurring climate fluctuations, nomad invasions, rural flight to cities, and outbreaks of disease kept the empire from recovering. This book is the first to look at the impact of climate on Middle East history and one of the first to look at the environmental evidence and interdisciplinary perspectives and offers a major reinterpretation of a central period in Ottoman history"-- Από τον εκδότη.